Guidance for Operational Risk Management in Government Debt Management - Magnusson, Tomas; Prasad, Abha; Storkey, Ian (World Bank, Washington, DC, 2017)
Operational risk is defined as the risk of loss resulting from inadequate or failed internal processes, people and systems or from external events. In debt management operations, the categories of risks, such as market risk, credit risk, refinancing risk and liquidity risk, are relatively well known; however operational risk is not. The area has not been given due attention to by government debt managers in developing a risk management framework. A similar conclusion on aspects pertaining to operational risk management is borne out from the early results of the World Bank's assessments using its government Debt Management Performance Assessment (DeMPA) tool. This paper thus, introduces the concepts of operational risk as applied to government debt management (DeM) and attempts to present a framework for debt managers to manage operational risks while undertaking public debt management operations. It draws on existing literature for operational risk management principles and practices that have been formulated by the Bank for International Settlements (BIS) Basel Committee on Banking Supervision, the Committee of Sponsoring Organizations (COSO) and the findings of the DeMPAs.